Nanoindentation and micro-mechanical fracture toughness of electrodeposited nanocrystalline Ni-W alloy films - Armstrong, D.E.J.; Haseeb, A.S. Md. Abdul; Roberts, S.G.; Wilkinson, A.J.; Bade, K. (2012)
Nanocrystalline nickel-tungsten alloys have great potential in the fabrication of components for microelectromechanical systems. Here the fracture toughness of Ni-12.7 at.W alloy micro-cantilever beams was investigated. Micro-cantilevers were fabricated by UV lithography and electrodeposition and notched by focused ion beam machining. Load was applied using a nanoindenter and fracture toughness was calculated from the fracture load. Fracture toughness of the Ni-12.7 at.W was in the range of 1.49-5.14 MPa root m. This is higher than the fracture toughness of Si (another important microelectromechanical systems material), but considerably lower than that of electrodeposited nickel and other nickel based alloys. (C) 2012 Elsevier B.V. All rights reserved.